In silico study and structure-activity relations of glucose-bound coumarin derivatives against the NSP12 protein of SARS-CoV-2 - Çelik, Esra; Özdemir, Mücahit; Yalçın, Bahattin; Köksoy, Baybars (Atatürk Üniversitesi, 2021)
In this study, designs of antiviral drug candidates that may be effective against SARS-CoV-2 virus were performed. Molecular docking was used to explore the effect of coumarin and its derivatives, which have antiviral action, on RNA polymerase NSP12, one of the key proteins of the coronavirus. The sugar group on coumarins was selected to increase hydrophilicity, and the amide groups were diversified to investigate selectivity. Coumarins containing 3-(p-phenylamidomorpholine), 3-(p-phenylamidopiperazine), and 3-(p-phenylamidopiperidine) groups had the best docking scores, with binding affinities of -10.1 kcal/mol, -10.1 kcal/mol, and -10.0 kcal/mol, respectively. The pharmacokinetic and toxicokinetic properties of compounds were estimated close to reality using various databases, and their values were close to the target values needed for a compound to become a drug. This study is also thought to give insight to scientists working for the design of SARS-CoV-2 antiviral drugs in terms of the structure activity relationship between coumarin and its functional groups.

Bu çalışmada SARS-CoV-2 virüsüne karşı etkili olabilecek antiviral ilaç adaylarının tasarımları yapılmıştır. Moleküler yerleştirme, antiviral etkiye sahip kumarin ve türevlerinin, koronavirüsün temel proteinlerinden biri olan RNA polimeraz NSP12 üzerindeki etkisini araştırmak için kullanıldı. Kumarinlerdeki şeker grubu, hidrofilisiteyi arttırmak için seçilmiş ve seçiciliği araştırmak için amid grupları çeşitlendirilmiştir. 3-(p-fenilamidomorfolin), 3-(p-fenilamidopiperazin) ve 3-(p-fenilamidopiperidin) gruplarını içeren kumarinler, sırasıyla -10.1 kcal/mol, -10.1 kcal/mol, and -10.0 kcal/mol bağlanma afiniteleriyle en iyi yerleştirme puanlarına sahipti. Bileşiklerin farmakokinetik ve toksikokinetik özellikleri, çeşitli veri tabanları kullanılarak gerçeğe yakın olarak tahmin edildi ve değerleri, bir bileşiğin ilaca dönüşmesi için gereken hedef değerlere yakındı. Bu çalışmanın ayrıca SARS-CoV-2 antiviral ilaçların tasarımı için çalışan bilim insanlarına kumarin ve fonksiyonel grupları arasındaki yapı aktivite ilişkisi açısından fikir vereceği düşünülmektedir.
SARS-CoV-2'nin NSP12 proteinine karşı glukoza bağlı kumarin türevlerinin in silico çalışması ve yapı-aktivite ilişkileri